HIGH PRESCRIPTION OF LOW MOLECULAR WEIGHT HEPARINS DURING PREGNANCY IN A HOSPITAL IN TETOVO, THE REPUBLIC OF MACEDONIA - Sihana Ahmeti Lika; Nagip Rufati; Merita Dauti; Ledjan Malaj (European Scientific Journal, ESJ, 2015)
Background: This study sought to explore the increase of usage of low molecular weight heparins (LMWH), for venous thromboembolism (VTE) treatment and prophylaxis during the period of pregnancy. Materials and methods: A retrospective study was undertaken during 01 January – 31 June of 2013, in the Department of Gynecology and Obstetrics, at Clinical Hospital in Tetova. Data were collected for the following: patient demographics, week and month of pregnancy, number of pregnancies for each patient, diagnosis, drug details and the cost for the entire period of hospitalization. Results: Over six months, the total number of pregnant women was 1020, from that number, 366 (35.88 %) were prescribed LMWH. Majority of patients given LMWH were aged 25-30, 196 (53.55 %). Clexane 2000 UI and Fraxiparine 0.4UI, were the most prescribed anticoagulant, 98 (26.78 %), respectly 97 (26.50 %) of patients received this therapy. The most common diagnosis that was foud in the study was nonpathologycal pregnancy asocciated with high levels of D-dimers 177 (48.36 %) patients. Conclusions: The results of this study indicate that there is an urgent need to improve the prescription of anticoagulants in the Department of Gynecology and Obstetrics, Clinical Hospital of Tetova, Republic of Macedonia.